MIRERC087/2025: Understanding Financial Behaviors and Designing Interventions for Economic Empowerment (2025–2030) - James Ogada; Mutwiri, Antony (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary Behavioral experiments offer a unique lens on human decision-making and development. Over the past decade, Busara has applied behavioral science across diverse disciplines to test solutions for poverty alleviation. For 10 plus years now, Busara has applied the use of behavioral science across disciplines to test behaviorally informed solutions and advance its application in the Global South context including Kenya. Indeed, we cannot downplay the promising nature of the use of behavioral experiments in international development. By uncovering behavioral barriers and enablers to development outcomes, experimental studies offer actionable insights for designing more effective, targeted interventions that resonate with the preferences and motivations of beneficiaries. In this five-year research program, Busara’s will run a study on behavioural experiments in financial inclusion including, but not limited to digital payments adoption, merchant behavior, SGB financing, behavioral credit scoring, digital financial literacy, asset financing, and access to clean energy. The study will use experiments, surveys, interviews, focus group discussions, observational methods, and pilot testing to uncover behavioral barriers and design solutions in these domains. The findings will generate evidence to inform more effective financial services and policies. This IRB protocol outlines the objectives, methodology, and ethical safeguards for all activities in this research.